2021
DOI: 10.1016/j.stemcr.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocytes recruit monocytes upon SARS-CoV-2 infection by secreting CCL2

Abstract: In the experimental procedures of the main text and in the supplemental information, the authors have now corrected the source of Golden Syrian hamsters to ''Charles River'' instead of ''Jackson Laboratory'' (the latter of which mistakenly appeared in the original version). The authors apologize for the confusion caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Besides, mild ischemia (early stages) is characterized by increased glycolytic flux with concomitant increased glucose uptake 48 . Furthermore, an in vivo study in hamsters infected with SARS-CoV-2 found increased expression of ROS-related genes in heart tissue 60 . Of note, viral transcripts were detected in the left ventricle and atrium, and the right atrium, but not the right ventricle; this suggests that the sampling site might matter.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, mild ischemia (early stages) is characterized by increased glycolytic flux with concomitant increased glucose uptake 48 . Furthermore, an in vivo study in hamsters infected with SARS-CoV-2 found increased expression of ROS-related genes in heart tissue 60 . Of note, viral transcripts were detected in the left ventricle and atrium, and the right atrium, but not the right ventricle; this suggests that the sampling site might matter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to using samples from COVID-19 patients for research, developing animal models for COVID-19 and subjecting them to scRNA-seq could facilitate preclinical analysis of vaccines and therapeutic agents. Although there are many studies using infected animals for COVID-19 research, 87,88 only a few studies performed scRNA-seq on COVID-19-infected animals like monkeys, 89 hamsters, 90 macaques, 91 ferrets, 92 and K18-hACE2 transgenic mice. 93 Several studies demonstrated the antiviral immune responses of animal models after receiving newly developed vaccines with scRNA-seq, [94][95][96][97] revealing induced gene modules of different immune cell populations.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…44 Ferroptosis of SAN-like pacemaker cells induced by SARS-CoV-2 infection might contribute to the pathogenesis of patients with COVID-19 and explain some of the cardiac arrhythmias observed in patients. Interestingly, although many types of cells/organoids, including hESC-SAN–like pacemaker cells, cardiomyocytes, 45 hPSC-derived lung alveolar organoids, 46 hPSC-derived pancreatic endocrine cells, 47 hPSC-derived liver organoids, 47 can be infected by SARS-CoV-2, ferroptosis is only detected in SARS-CoV-2–infected hESC-SAN–like pacemaker cells, indicating a cell type–specific response to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%